Fotokimia dan Farmakologi Daun Alpukat (Persea americana mill.) pada Aktivitas Antihipertensi - Husnandari, Aqila; Carolia, Novita; Putri, Giska Tri; Rahmanisa, Soraya (Medula, 2025)
Hypertension is the number one generative disease in the world that has blood pressure of more than 140/90 mmHg. Hypertension without therapy will become chronic and complicated. Therapy carried out for a long period of time causes a fairly high risk factor so that herbal therapy becomes an alternative. This literature review aims to determine the photochemistry and pharmacology of avocado leaves (Persea americana mill.) On antihypertensive activity. Photochemistry contained in avocado leaves can lower blood pressure in the form of flavonoids, saponins, tannins, alkaloids, steroids, and terpenoids. The method used is to review journal articles that have been published in Google Scholar and Pubmed. Using keywords such as "photochemistry, pharmacology, avocado leaves, and antihypertensive activity" 231 scientific articles and journals were obtained. This review article uses 10 selected scientific articles and journals. Experimental studies show that there are pharmacological functions that fight hypertension, which means that they can lower blood pressure.